The Concept of Liberal Feminism in Mary Wollstonecraft's Novel Nglari Woting Ati by Fitri Gunawan - Mariska, Fayza; Widihastuti, Rahma Ari (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study is to analyze Mary Wollstonecraft's Concept of Liberal Feminism in the Novel Nglari Woting Ati by Fitri Gunawan. Women are often portrayed as the main characters in literary works, one of which is in the novel Nglari Woting Ati by Fitri Gunawan. This novel tells the story of a woman named Muherdini's struggle to achieve her academic goals without abandoning her role as a wife and mother. The novel Nglari Woting Ati will be studied and analyzed from the perspective of Mary Wollstonecraft's liberal feminism. The purpose of this study is to describe how the character Muherdini reflects Mary Wollstonecraft's liberal feminism and the attitudes of other characters as a result. The research method uses an objective approach based on Mary Wollstonecraft's liberal feminism theory. The primary data source used is the novel Nglari Woting Ati. The research data consists of quotations, dialogues, and narratives that contain elements of Mary Wollstonecraft's liberal feminism. The data collection technique used was semiotic reading. The analysis technique used was hermeneutic reading. The results of the study show that the main character practices liberal feminism in the form of intellectual development, the elimination of gender double standards, and the right to better employment. Additional characters affected by liberal feminism include Irawan, who is convinced that Muherdini deserves a higher education; Ardhana, who imitates Muherdini's traits and grows into a child who enjoys trying new things; Mbak Laras, who does not restrict Muherdini's education and career and grants her freedom; Bu Siti, who admires Muherdini and regards her as her own daughter; and Anita, who feels inferior to Muherdini.https://jurnal.usk.ac.id/riwayat